(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The purpose of this study was to examine the “Suryanamaskar program on core fitness of interschoolkickboxing players”. Experimental design was used for this study to check the hypothesis thisresearch was based on pre-test post- test non equivalent groups design. The present research wholesample a total number of 24 boys inter-school kickboxing players those represent the Ahmednagardistrict to State National level were selected who had failed into three to six test items on the basis ofpurposively method of sampling technique from kickboxing district sports association and clubs ofAhmednagar. The study was selected the variables of core strength Kraus-Weber’s minimum muscularfitness test consist of six items which indicate the level of muscular strength and flexibility of keymuscle group. The researcher gathered the subjects and given to them instruction about the importanceabout study and explain Suryanamaskar program Kraus - Weber tests. The implemented pre-test byKraus -Weber minimum muscular fitness tests and six weeks Suryanamaskar program which was givenfive days in a week was manipulated only on experimental group not control group. After Suryanamaskarprogram both group’s i.e, experimental and control groups, were post tested for data collection. Theresearcher concluded that six weeks Suryanamaskar program was significantly effective on core fitnessimproved of inter-school kickboxing players which indicate the level of muscular strength and flexibilityof key-muscle groups and also the findings of this study may be helpful to the inter-school kickboxingplayers to doing regular practice of Suryanamaskar to improve their health and fitness.